P-wave anelasticity in hydrate-bearing sediments based on a triple-porosity model - Ba, Jing; Guo, Fulin; Carcione, José M.; Gei, Davide (Frontiers in Earth Science, 2023)
P-wave anelasticity (attenuation and dispersion) of hydrate-bearing sediments depends on several factors, namely the properties of the mineral components, hydrate content and morphology, and fluid saturation. Anelasticity is analyzed with a triple-porosity model (stiff pores, clay micropores and hydrate micropores), by considering hydrate as an additional solid skeleton. We relate the hydrate volume ratio, porosity and radii of the hydrate inclusion and clay mineral to the P-wave velocity and attenuation. The model takes wave-induced local fluid flow (mesoscopic loss) at the grain contacts into account. The results are compared with those of a double-porosity and load-bearing models, and verified with well-log data from ODP sites 1247B and 1250F, and data reported in Nankai Trough, Japan. Model results and data show a good agreement.